ECONOMIC EMPOWERMENT OF COASTAL COMMUNITIES THROUGH FISHERMAN INSURANCE - Riaman Riaman; Sukono Sukono; Kalfin Kalfin (International Journal of Research in Community Services, 2020)
The current condition of fishermen in Indonesia is still far from prosperous, especially small fishermen who generally have an income of less than one million/month. Fishermen are faced with constraints on the characteristics of their fishing business which depend on climate change, weather uncertainty, and sea waves, so they pose a high risk. This affects the low income of these fishermen because fishermen working hours are very dependent on the weather so if the sea waves are high or other bad weather, fishermen are forced not to go to sea. Therefore, it is necessary to protect fishermen through fisherman insurance. Currently, the government has been trying to increase the target of fish production and consumption through protection and welfare for fishermen. One of the efforts to improve fishermen's welfare is a work program that guarantees protection against risks to fishermen, fish cultivators, and salt farmers. This program targets 1 million insurance for fishermen spread across the territory of the Republic of Indonesia. One of the government's efforts to protect fishermen and their families is through the provision of Insurance Premium Assistance for Fishermen. This effort is intended to provide guaranteed protection against risks experienced by fishermen, such as death, permanent disability, and medical costs; as well as provide awareness of insurance for fishermen. However, currently, fishermen's income is not included in the risk guarantee from the fishermen’s insurance program. Even though the income of fishermen is one of the criteria for measuring the economy of coastal communities who work as fishermen and indirectly can determine the maritime economy. Therefore, we as academics intend to conduct training and socialization of economic empowerment of fishing communities based on knowledge, skills, and potential in Cirebon Fishermen Village through Community Service programs. The material that will be provided in this Community Service activity is related to the economic empowerment of fishermen communities and community-based fisherman insurance. This material will be given to the workshop session both to the local community.